25th AIAA Applied Aerodynamics Conference 2007
DOI: 10.2514/6.2007-3803
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Framework for Fluid Structure Interaction in Biologically Inspired Flapping Flight

Abstract: Although there are many examples of successful flapping flight in nature, engineers and scientists have had difficulty achieving high performance levels using flapping wing designs. In this paper a computational framework to design and analyze flapping flight for Micro Aerial Vehicle size scales is presented. This computational framework exploits a series of different geometric and physical fidelity level representations. The tools considered are wake only methods(HallOpt), lifting line methods(ASWING), panel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 23 publications
0
34
0
Order By: Relevance
“…The aeroelasticity of flapping wings has only recently been seriously addressed and a full picture of the basic aeroelastic phenomena in flapping flight is still not clear [1,5,[11][12][13][14][15][16][17][18][19][20][21]. In an earlier investigation, Smith [14] has studied the effects of flexibility on the aerodynamics of Moth wings by modeling them as linearly elastic structures using finite elements for a Reynolds number of the order of 10 3 and reduced frequencies of the order of 0.2 and higher.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The aeroelasticity of flapping wings has only recently been seriously addressed and a full picture of the basic aeroelastic phenomena in flapping flight is still not clear [1,5,[11][12][13][14][15][16][17][18][19][20][21]. In an earlier investigation, Smith [14] has studied the effects of flexibility on the aerodynamics of Moth wings by modeling them as linearly elastic structures using finite elements for a Reynolds number of the order of 10 3 and reduced frequencies of the order of 0.2 and higher.…”
mentioning
confidence: 99%
“…However, when the wing is immersed in water, the chordwise flexibility increased the efficiency and the spanwise flexibility reduced both the thrust and the efficiency. Wills et al [17] have presented a computational framework to design and analyze flapping MAV flight. A series of different geometric and physical fidelity level representations of solution methodologies was described in the work.…”
mentioning
confidence: 99%
“…In order to show the role of the wing's flexibility in the production of lift, the parameters that regulate the deformation were tuned in order to increase the lift force throughout the stroke cycle with respect to the rigid-wing model. The set of initial conditions for the two cases studied consists of a body angle of 75 and a stroke plane angle of 15 . These values produce a horizontal stroke plane.…”
Section: Dynamics Of Flapping Wingsmentioning
confidence: 99%
“…The primary components of numerical simulations are the aerodynamic solver, the structural-dynamic solver, and the communication between them. Early studies on fluid-structure interactions for vehicles with flapping wings have been based on either two-dimensional models or other simplified aerodynamic models based on thin-airfoil theory or unsteady panel methods or Euler methods and on linear beam finite elements [14][15][16][17]. Nakata and Liu [18] used an unsteady aerodynamic model based on a Navier-Stokes solver [19] coupled with a finite-element formulation specifically developed for insect flight that accounts for the distribution and anisotropy of the wing's veins and membranes.…”
Section: Introductionmentioning
confidence: 99%
“…We choose the later strategy, and use a multi-fidelity framework that comprises a wake-only method, a quasi-doublet lattice method for inverse wing design and a high fidelity Navier-Stokes simulation. We have shown that our particular multi-fidelity approach is promising for both two-dimensional and three-dimensional settings such as thrust producing flapping foils 1,2 . We present a similar framework here for designing efficient wings and validating those designs at the highest fidelity level.…”
Section: Introductionmentioning
confidence: 99%